(3aJM GdhgGH TQM efgL GdWdGHs - (3GdSfjcj, GdeUQj, GdTGaYqj, CHh jMji, TjN GdESdGe, RcQjG Hf eMeO Hf CMeO Hf RcQjG, J (B926 (3g`s ((3SdjeGf Hf Ydj GdOefjs)
(3ChdgG (B:s
(3cJGH GdLfGjI GdTGedI ddLfGjI HGdLGQM hHZjQg cSMQ heKbd agj CYe ef JYHjQg HGdLQGM hGdCUd ajgG BjGJ cBjI jG CjgG GdPjf BefhG cJH Ydjce GdbUGUs
(3BNQgG (B:s
(3hEf MedJ Hg ef SjOgG aj eQV ehJg Ch ChUi HYJbgG ef GdKdK cEfaGb GdeGd aj GdTghGJ adG jDKQ ajg Pdc HNdGa eG dh ChUi HMLI GdESdGe ef GdKdK hgPG ef RjGOJj aj GdhdOs
(3aj BNQg QSGdI dTeS GdOjf eMeO GdQedj JYdjb Ydi bGYOI JHYjI GdaQY GdCUds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 46s
(3eYLe GdeDdajf (B1 / 733s
(3cTa GdXfhf (B2 / 1875s
(3TPQGJ GdPgH (B8 / 134s
Keywords: (3Gdabg GdTGaYjs